2021
DOI: 10.1016/j.isci.2021.102735
|View full text |Cite
|
Sign up to set email alerts
|

High-entropy R2O3-Y2O3-TiO2-ZrO2-Al2O3 glasses with ultrahigh hardness, Young's modulus, and indentation fracture toughness

Abstract: Glasses with high hardness, high Young's modulus, and high fracture toughness become crucial materials which are urgently needed in the protective covers for various electronic displays. Here, a paradigm is presented that the conceptual design of high-entropy materials is adaptable to high performance oxide glasses. We designed the multi-component glass compositions of 18.77R 2 O 3 -4.83Y 2 O 3 -28.22TiO 2 -8.75ZrO 2 -39.43Al 2 O 3 (R = La, Sm, Gd) and elaborated successfully the glassy samples through a conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…These are larger than those of SiO 2 (68.8 kJ/cm 3 ) and B 2 O 3 (86.0 kJ/cm 3 ) 7 . In addition, it has been reported that high field ions can induce the transformation of Al 3+ into a higher coordination number 8,13,16 . In aluminosilicate glasses, which typically range from 3% to 30% and from 1% to 2%, respectively, 17 these high‐entropy glasses reach values near 41.9% and 14.0% 8 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are larger than those of SiO 2 (68.8 kJ/cm 3 ) and B 2 O 3 (86.0 kJ/cm 3 ) 7 . In addition, it has been reported that high field ions can induce the transformation of Al 3+ into a higher coordination number 8,13,16 . In aluminosilicate glasses, which typically range from 3% to 30% and from 1% to 2%, respectively, 17 these high‐entropy glasses reach values near 41.9% and 14.0% 8 .…”
Section: Resultsmentioning
confidence: 99%
“…11 The "cocktail" effect of high entropy has led to unexpected improvements in performance. 12 A prime example of this innovative approach is the high-entropy glass created by Li et al, composed of 18.77R 2 O 3 -4.83Y 2 O 3 -28.22TiO 2 -8.75ZrO 2 -39.43Al 2 O 3 , 13 which achieves a Young's modulus of 177.9 GPa. However, the refractive index remains below 2.0.…”
Section: Introductionmentioning
confidence: 99%
“…[159,160] Recently, the mixing of five or more oxide components (to achieve so-called "high-entropy" materials) has also been proposed for glasses, demonstrating the containerless synthesis of a (La,Sm,Gd) 2 O 3 -Y 2 O 3 -TiO 2 -ZrO 2 -Al 2 O 3 glass with high hardness (>12 GPa) and high Young's modulus (>170 GPa). [161] For such ultrastiff glasses (which usually rely on heavy loading of rare earth oxides), it is challenging is to adapt their composition in such a way that larger glass objects can be produced. It typically means that the number of chemical components must be increased, for example, such as in the popular alkaline earth aluminosilicate glasses, which may accommodate high amounts of rare earth doping and still be meltable by regular laboratory techniques.…”
Section: Oxide Glasses From the Bottom-upmentioning
confidence: 99%
“…Copyright 2018, Elsevier and Reproduced with permission [207]. Copyright 2018, Elsevier), and Reproduced with permission under the terms of a Creative Commons Attribution License (CC BY-NC-ND 4.0) [161]. Copyright 2021, The Authors, published by AAAS.…”
mentioning
confidence: 99%
“…Recently, the highest Young's modulus of 171 GPa and Vickers hardness of 13 GPa, measured using a nanoindenter method, have been reported for high entropy oxide glasses prepared using a levitation technique. 115) Note that Young's modulus and other mechanical properties often strongly depend on measurement methods.…”
Section: High Hardnessmentioning
confidence: 99%